Basquiat the unknown notebooks ; [on the occasion of the exhibition ... held at the Brooklyn Museum, April 3 - August 23, 2015] - Buchhart, Dieter 1971-; Bloom, Tricia Laughlin (Skira Rizzoli, 2015)
Accompanying a major traveling exhibition, this first-ever survey of the rarely seen notebooks of Basquiat features the artist's handwritten notes, poems, and drawings, along with related works on paper and large-scale paintings. With no formal training, Jean-Michel Basquiat (1960-1988) succeeded in developing a new and expressive style to become one of the most influential artists in the postmodern revival of figurative during the 1980s. In a series of notebooks from the early to mid-1980s, never before exhibited, Basquiat combined text and images reflecting his engagement with the countercultures of graffiti and hip-hop in New York City, as well as pop culture and world events. Filled with handwritten texts, poems, pictograms, and drawings, many of them iconic images that recur throughout his artwork-teepees, crowns, skeleton-like silhouettes, and grimacing masks-and these notebooks reveal much about the artist's creative process and the importance of the written word in his aesthetic. With over 150 notebook pages and numerous drawings and paintings, this important book sheds new light on Basquiat's career and his critical place in contemporary art history
Keywords: Basquiat, Jean Michel -- 1960-1988; Geschichte 1980-1987; Geschichte 1980-1986; Zeichnung; Skizzenbuch; Notizbuch; Ausstellungskatalog -- Brooklyn Museum -- 03.04.2015-23.08.2015 -- New York, NY